Sustainability Status of Vaname Shrimp (Penaeus vannamei) Pond in Coastal Areas of Lamongan Regency - Destrina Elita Koto; Asus Maizar Suryanto Hertika; Jati Batoro (Jurnal Penelitian Pendidikan IPA, 2025)
Lamongan Regency was the largest center of the fisheries in East Java.  Lamongan Regency only has two type of operation ponds: traditional brackishwater pond and semi-intensive brackishwater pond. Aquaculture in Lamongan District still relies on traditional fisheries. Whiteleg shrimp (Penaeus vannamei) as a Indonesia`s leading aquaculture commodities can have a positive impact on coastal communities, especially in economic and social aspects but does not have sustainable waste management. In this study, a multidimensional scalling (MDS) method was used to analyze the ecological, economi, social, technology and institutional dimension. The study was conducted during February – May 2025, primary data collection was carried out throught interview respondens and the secondary data from related data references. The result of the study showed that the sustainability values range both 48,57 – 55,82 (ecological dimensions), 60,83 – 67,60 (economic dimensions), 55,48-66,70 (social dimensions), 54,79 – 57,57 (technological dimensions), and 50,83 – 57,90 (institutional dimensions). The averages value of sustainability index of vaname shrimp (Penaeus vannamei) Pond in Coastal Areas of Lamongan Regency was quite sustainability. Based on leverage analysis, sensitive attributes obtained in this study were ecological dimensions (1) influence are the level of pollution, (2) pest attacks and (3) water quality management, economic dimension (1) availability of capital resources, (2) marketing prices (RMS = 4.0), and (3) impact on income , social dimension (1) interaction patterns, (2) training and socialization and (3) cultivation knowledge technological dimensions (1) wastewater treatment plant (WWTP) technology, (2) machine automation, and (3) the availability of facilities and infrastructure, and institutional dimensions (1) monitoring and evaluation